PERFORMANCE ASSESMENT EVALUATION EMPLOYEES USING METHOD SIMPLE MULTI ATTRIBUTE RATING TECHNIQUE (SMART) AT THE MEDAN FINANCIAL TRAINING CENTER - Wira Afandi , Fikry; Deasy; Alifiah, Nasya; Citra Amanda; Ratna Sari, Desi (Journal of Mathematics and Scientific Computing With Applications, 2025)
Employee performance assessment is one of the important aspects to achieve the goals of an institution. With the application of information technology, a decision support system can be used to provide assessments. One method that can be used to provide employee performance assessments is the SMART (Simple Multi Attribute Rating Technique) method. This method was chosen because of its superiority in being able to solve problems using multicriteria so it is suitable for determining employee performance assessments at the Medan Financial Training Center. The criteria used in determining employee performance assessments at the Medan Financial Training Center are Discipline, Responsibility, Leadership, Innovation, Competence. Data collection was carried out using questionnaires distributed to employees at the Medan Financial Training Center. The results of the study from 20 data samples using the SMART method obtained ranking results from employee performance assessments ranging from very good assessments with a final value of 1 to very poor with a final value of 0.025.